English Adjectival Predicates Taking Subjunctive Complements: What to Change in Curricula - Eugenia Romanova; Anna Oveshkova (Journal of Language and Education)
Background: Similar projects have been undertaken before with the objective to improve English instruction. However, our work is different in that a) it is based on formal theoretical premises; b) the range of the studied data goes far beyond any analogous paper; c) we compare the subjunctive uses to those of indicative and modal auxiliaries; d) we focus on adjectives and their variable selectional properties concerning the mood in complement clauses.